High-Temperature Wireless Sensor Platform Powered by Energy Scavenging - Shane Winters; Nikung Thapa; Luke D. Doucette; Jonathan Kincaid; Qingsong Cui; Nuri W. Emanetoglu; Mauricio Pereira da Cunha (IEEE Open Journal of Industry Applications)
This article reports on the development of key components required for a self-powered oscillator unit designed to wirelessly transmit its signal under full insertion in high-temperature (HT) harsh-environments (HE), such as those present in power plants and industrial settings (metallurgic, oil extraction, molding, and aerospace). The oscillator employed a silicon carbide power transistor and HT passive components on a screen-printed alumina circuit board capable of operation beyond 300 °C. The HT oscillator circuit was powered solely by in-situ energy-scavenging thermoelectric generator (TEG) modules using passive cooling, eliminating the need for an external power supply or active cooling. In addition, a silicon-based external booster circuit was used to achieve the required TEG voltage regulation to test the TEG-powered HT oscillator circuit. The TEG-powered oscillator circuit was tested inside a nonmetallic furnace from room temperature to over 300 °C for transmission of a wireless signal, which was detected outside the furnace at 11 ft (3.4 m). Such a wireless transmitting system powered only by in-situ TEGs, with no requirement for external power or active cooling, is very attractive for flexible, mobile standalone control and sensor units targeted for operation in HT HE conditions found in power plants and industrial settings.